THE MINIMUM RADIUS DOMINATING ENERGY OF A GRAPH - Nanjundaswamy M; Nayaka S R; Puttaswamy; Siddaraju; Purushothama S (Utilitas Mathematica, 2025)
Let ???? be a graph of order n. A dominating set ???? is said to be a radius dominating set if for each vertex u not in S there exists a vertex v in S such that ????(????,????)=????????????(????). The cardinality of the minimum radius dominating set is called the radius domination number; ????????????(????). The energy of a graph is closely related to the energy of the chemical structure whose graphical representation is isomorphic to ????. In this article, we shall consider a new energy parameter is defined and studied for standard families of graphs, also established some bounds.